Perceptions of the impact of COVID-19 in Tennessee, USA: a retrospective study - Chavez-Lindell, Tamara L.; Cahill, Katie A.; Kintziger, Kristina W.; Odoi, Agricola (PeerJ, 2023)
Background Despite high incidence and mortality risks associated with COVID-19 during the pandemic, stay-at-home orders and vaccination recommendations were met with varying levels of acceptance in Tennessee. Understanding perceptions of individuals regarding the health and economic impacts of COVID-19 is necessary to address public concerns while ensuring appropriate public health response. Therefore, the objectives of this study were to (a) investigate differences in opinions among residents of Tennessee regarding the impacts of COVID-19; and (b) identify socioeconomic and demographic predictors/determinants of these opinions. Methods This retrospective cross-sectional study was conducted using survey data collected in nine waves during 2020. Distributions of survey-weighted sociodemographic characteristics and respondent perceptions of the impact of COVID-19 were computed. Weighted logistic models were used to investigate predictors of a number of perceptions: whether the health or economic impact was greater, concern for respondent’s health, concern for family’s health, and willingness to accept COVID-19 vaccine. Results The study included a total of 9,754 survey respondents. Approximately equal percentages considered COVID-19 to have a greater economic (48.4%) versus health impact (51.6%). Just 40.1% of the respondents reported that they would definitely accept a COVID-19 vaccine. Age group, race, educational attainment, and household composition were significant (p < 0.05) predictors of all investigated perceptions regarding COVID-19. Lack of prior infection was the strongest predictor of the perception of COVID-19 having a greater impact on health (OR = 2.40, p < 0.001), concern for respondent’s health (OR = 1.86, p = 0.002), and concern for family members’ health (OR = 1.90, p = 0.001). Compared to males, females had higher odds of identifying the health impact of COVID-19 as greater (OR = 1.09, p = 0.041) and reporting concern for family health (OR = 1.14, p = 0.003). However, they had lower odds (OR = 0.63, p < 0.001) of willingness to accept vaccine than males. Conclusion These findings improve our understanding of the drivers of health behaviors, including vaccine hesitancy, and are useful for guiding public health outreach/education programs.
Keywords: COVID-19; Tennessee; USA; Impact; Questionnaire survey; Retrospective; Cross-sectional study; Logistic regression; Perceptions